Navigating “cruel optimism”: Parental vigilance and dilemmas of social mobility in Singapore’s educational landscape - Göransson, Kristina (Cultural Dynamics, 2025)
In Singapore, children’s education is often presented as “an overriding and all-consuming concern,” driven by intense competition for grades and school admissions (Waters, 2015: 290). However, the desire for academic excellence as a pathway to better lives is not as straightforward as it may seem. Drawing on ethnographic fieldwork with Singaporean families, this paper explores parents’ affective and productive labor in navigating the emerging tensions between aspirations for academic achievement on one hand, and school-life balance and happiness on the other. It examines how parents actively manage these conflicting aspirations, drawing on Lauren Berlant’s (2011) concept of “cruel optimism”—a state marked by significant anxiety over the unfulfilled promises of modernity and neoliberalism. This is particularly evident in affective attachments to fantasies of “the good life,” such as upward social mobility, job security, or freedom— understood as a “proactive, hopeful affective force that remains open and indeed seeks out possibilities for change” (Sotirin, 2020: 12). In examining how parents resist, (re)negotiate, and even reconcile these ambivalent aspirations regarding their children’s education, this paper explores the affective landscape underpinning vigilance and the reconfiguration of upward social mobility.